A Survey of Classroom Facilities at Private Primary Schools in Mardan - Shumaila Gul; Dr. Hafiz Muhammad Irshadullah; Dr. Muhammad Idris (Dialogue Social Science Review (DSSR), 2025)
A survey of classroom facilities at private primary schools in Mardan was a new study. In this research study the following research objectives were: (1) To investigate classroom facilities (organizational) at private primary schools in Mardan; & (2) To inquire classroom academic facilities at private primary schools in Mardan. In this research work the following research questions were tested: (1) what are the organizational facilities in the classroom at private primary school in Mardan? and (2) what are the academic classroom facilities at private primary schools in Mardan? All the (15) Private Primary Schools in Village Gujrat were the population in this study. A sample of (62) Private Primary Schools Teachers in Village Gujrat was selected randomly. In which the following respondents were included. A closed-ended questionnaire with three options was developed. The instrument was validated from the experts. The reliability of instruments was calculated 0.79. This study was delimited to the village Gujrat in District Mardan. Based on the examination, the classrooms are well-lit, specious, hygienic, equipped with wall clocks, fans, teaching kits, whiteboards, multimedia, a syllabus, and visual aids. it was suggested that classroom facilities be updated to reflect current technology developments. Additionally, classrooms may be highly effective academically for teaching and learning.